Reliability assessment of the collision between marine risers - He, Jianwen (2014)
As offshore production shifts to deep water, riser systems become more vulnerable. Riser clashing is a critical issue needed to be addressed in the design stage. Two design principles are defined in the code and termed as no collision allowed and collision allowed. Hydrodynamic interference is found to be the main driver of riser collision. This thesis proposes practical approaches to evaluate the probability of failure due to riser collision. With this important parameter, designers can optimally determine the riser layout. The whole work is separated into three stages.